34 Leadership conversations. (3rd November 2019) - Swanwick, Tim; Hardman, Louisa; Szram, Jo
Abstract : The leadership of systems of care is increasingly recognised as a core clinical activity for all healthcare professionals. The GMC expects all postgraduate medical training programmes to equip trainees with leadership capabilities. But many supervisors feel ill equipped to 'teach' leadership and lack confidence to hold formative conversations in this domain. In 2017, HEE published a report on leadership development for doctors in postgraduate medical training identifying a need for 'faculty to think differently about their role and to be more confident in brokering leadership learning.' Three existing 'training the trainer' programmes were identified all with slightly differing approaches. Further needs analysis was conducted during 2018 through further focus groups of supervisors and trainees. As a result of the above, a prototype training the trainers programme was designed alongside a comprehensive resource pack. This was piloted and then underwent 8 iterations. Each session was delivered by a member of NHS Leadership Academy faculty in partnership with a local clinician educator to a mixed audience of supervisors and senior educators. Following each session, resources were amended in the light of feedback. A final version was arrived at in May 19 with an emphasis on enhancing developmental interactions between trainees and trainers: 'Leadership Conversations'. The half day programme offers supervisors practice and structured guidance to enable them to integrate leadership learning into their regular discussions with trainees. It familiarises supervisors with a new resource pack, encouraging supervisors to use it for their own leadership learning as well as for trainees. The sessions have evaluated well with feedback used to further modify the product. The programme - slide deck, trainers notes and resource pack – has since been disseminated for local delivery. Further evaluation and regular updates are planned including four accompanying short films due Oct 19.